Teaching careers of black woman in higher education: A scope review (Contextus - Revista Contemporânea de Economia e Gestão, 2024)
Background: The inclusion of black women as teachers in higher education breaks with several social standards, especially in the search to establish their places in society and at work. Furthermore, these women face many obstacles in achieving advancement in their teaching careers.Purpose: This study aimed to identify how the teaching career of black women in higher education has been portrayed by international scientific literature.Method: The method used was a literature scoping review, carried out on the Web of Science (WoS) data platform. The work was carried out following the instructions (with necessary adaptations) from the Joanna Briggs Institute (JBI). 124 documents were recovered, including articles from scientific journals, book reviews, books, book chapters, editorials, among others. After inserting the inclusion and exclusion criteria, 14 texts were selected.Results: The results were highlighted in five categories, namely: (i) career as a retrospective construction of meaning; (ii) career as a means of linking different levels of social complexity; (iii) career as a trajectory in space and time; (iv) career as self-construction; and (v) career as a product rather than a process. From this perspective, the work found that studies of this nature have still been little produced.Conclusions: The study contributes by showing that theoretical categories make it possible to explain the empirical realities observed by other researchers. Furthermore, they serve as an instrument for organizing the contents evidenced by scientific literature, in order to structure them systematically.